221k views
4 votes
0 = 5x2 - 2x + 6

x= 1 +/- 3i/2
x=1 +/- (square root 11) /5
x=1 +/- i (square root 29) /5

1 Answer

3 votes

Answer:

Last option

Explanation:

Since we can't factor out the quadratic, we need to use quadratic formula to solve this:
x = (-b +/- √(b^2 - 4ac) )/(2a)

a = 5

b = -2

c = 6


x = (2 +/- √((-2)^2 - 4(5)(6)) )/(2(5))


x = (2 +/- √(4 - 120) )/(10)


x = (2 +/- √(-116) )/(10)


x = (2 +/- 2i√(29) )/(10)


x = (1 +/- i√(29) )/(5)

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.